Written evidence and the absence of witnesses : the inevitability of conviction in Chinese criminal justice - Yu, Mou (2015)
Through analysis based on an empirical study of the Chinese criminal process, this thesis examines the underlying reasons that lead to a striking feature of criminal trials in China---the absence of witnesses. The Chinese criminal justice system routinely relies on official written dossiers to determine the guilt or innocence of the accused. To investigate whether the constructed written evidence is truly reliable, participant observation and semi-structured interviews have been conducted to explore how these investigative dossiers are created, scrutinised and utilised at different stages of the criminal process. Themes that emerge in this study include the police's manipulation and fabrication of written statements, prosecutors' acceptance of, and even encouragement of, police malpractice in falsifying evidence, coerced prosecutorial interrogation in pursuit of a guilty plea, the pro forma trial process, predetermined judicial outcomes based on the official dossier produced and marginalised defence practice throughout the criminal process. Approaching the enquiry from an internal perspective of the legal institutions for the first time within empirical research, this study outlines the key issues with the Chinese criminal justice system through examination of the strategic inter-relationships between the key legal actors, the deep-seated legal culture embedded in legal actions and the structural injustices that follow. Positioning these findings within the Chinese socio-political context, this study reveals that the criminal justice system in China is not a precise truth-finding process, but serves as a State apparatus of social control. The criminal justice system has been structured through the Appraisal System, bureaucratic management, and the central value of collectivism in such a way as to maintain the stability of the authoritarian regime. None of China’s criminal justice institutions are capable of functioning independently to protect innocent individuals from being wrongly accused and convicted. Thus, wrongful convictions should not be seen as aberrational or exceptional, but as an inevitable outcome of established deficiencies.